Manajemen Pembelajaran TeFa untuk Meningkatkan Kompetensi dan Jiwa Enterpreuner Siswa Teknik Kendaraan Ringan SMK - Ananda, Enjela Dwi; Yulastri, Asmar; Maksum, Hasan; Yuliana, Yuliana (Juwara: Jurnal Wawasan dan Aksara, 2024)
Teaching factory has several main objectives, namely increasing the competence of SMK graduates, fostering entrepreneurial spirit, and producing products in the form of goods or services that have added value. This research applies a qualitative approach with a descriptive design. The data obtained were then analyzed using non-statistical descriptive methods to explore information about the implementation of teaching factory learning management to improve the competence and entrepreneurial spirit of students majoring in light vehicle engineering at SMK. The results of this study are (1) Implementation of Teaching Factory Learning Management: Comprehensive planning and a solid organizational structure are clearly visible, with implementation in accordance with industry standards. However, evaluation based on achievement analysis still needs to be improved; (2) Supporting and inhibiting factors: Infrastructure that meets industry standards and qualified teaching staff are the main supporting elements. Challenges faced include the mismatch between planning and implementation time, and limited collaboration with industry. Proposed solutions include implementing a block scheduling system and increasing partnerships with relevant industry sectors; (3) Effectiveness Evaluation: The assessment of Teaching Factory learning management shows that the program is efficient and effective in developing entrepreneurial spirit among students.